1991
DOI: 10.1007/bf02310920
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional requirements and growth characteristics of a biosurfactant-producingRhodococcus bacterium

Abstract: The nutritional requirements and growth characteristics of a biosurfactant-producingRhodococcus bacterium isolated from Kuwaiti soil were determined. Maximum cell yields (6.6 g/l) and biosurfactant production were achieved with a medium containing 2% (v/v)n-paraffin as a carbon and energy source, 0.2% lactose broth, optimal concentrations of nitrogen (nitrate), phosphorus, iron, magnesium and sodium sources, and minimal concentrations of potassium and trace element sources. The optimal pH was 6.8 for surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…Naitali et al (1989) reported a reduction in interfacial tension of hexadecane from 26.1 to 23 mN m -1 by Pseudomonas fluorescens and 10 mN m -1 by Alcaligenes faecalis respectively. Biosurfactant produced by Rhodococcus sp., is known to decrease both, surface and interfacial tension to 27 and 1.8 mN m -1 , respectively (Abu-Ruwaida et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Naitali et al (1989) reported a reduction in interfacial tension of hexadecane from 26.1 to 23 mN m -1 by Pseudomonas fluorescens and 10 mN m -1 by Alcaligenes faecalis respectively. Biosurfactant produced by Rhodococcus sp., is known to decrease both, surface and interfacial tension to 27 and 1.8 mN m -1 , respectively (Abu-Ruwaida et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…[18]. The nutritional requirements and growth characteristics of a biosurfactant-producing Rhodococcus bacterium isolated from Kuwaiti soil have been determined [39]. While, Espuny et al [40] reported a growth-dependent production of biosurfactant by Rhodococcus sp.…”
Section: Optimisation Of Productionmentioning
confidence: 98%
“…The lyophilized material was designated the acid precipitate and analyzed by thin-layer chromatography [1]. All organic solvents used were commercially distilled and of the highest available purity (Sigma-Aldrich).…”
Section: Surfactant Isolationmentioning
confidence: 99%
“…According to Bodour and Maier [9], the criterion used for selecting biosurfactantproducers is the ability to reduce the surface tension below 40 mNm - 1 . Also, Willumsen and Karlson [56], a criterion cited for emulsion-stabilizing capacity is the ability to maintain at least 50% of the original emulsion volume 24h after formation.…”
Section: Characterization Of Isolatesmentioning
confidence: 99%
See 1 more Smart Citation